Evolução de úlceras vasculares e o contexto do atendimento na rede municipal em uma cidade do interior do Brasil - Malaquias, Suelen Gomes (2014)
Analyze the conditions of care to people with vascular ulcers and the evolution of venous ulcers and associated factors among users of the public healthcare system in an interior city. The research integrated a cross- sectional design with a cohort study, developed from July 2011 to October 2013, in an interior Brazilian Midwest city. It involved people with vascular ulcers, the wound dressing units where this population was cared for and nursing professionals who worked there. Data were collected using interviews, clinical examinations, the Pressure Ulcer Scale Healing (PUSH), planigraphy, photographic records of the lesions, samples collected from the lesions for microbiological analysis, and a script for observation of the units. The greatest ulcer was elected as the main lesion. Criteria were established to detect ulcers considered to be infected and to classify the risk for cross- contamination in the units. A questionnaire was used to approach the nursing professionals. Associations were analyzed using a marginal homogeneity test, McNemar and the chi-square test, with p<0.05. The research proposal was approved by the Research Ethics Committee of the Federal University of Goiás (protocol 026/2011). Initially,31 people with vascular ulcers undergoing treatment at the 13 wound dressing units of the studied city were included. All units presented conditions classified as highly susceptible to cross- contamination. Of the 31 assessed ulcers, 29 (93.5%) presented evidence of infection. Samples could be collected from 25 lesions, and a positive result in culture was found for 23 (92.0%), with presence of one to three microorganisms. Seven (20.0%) occurrences were found for oxacillin- resistant staphylococcus, four (11.4%) forampicillin-resistant enterococci, and two (5.7%) for beta-lactam-resistant pseudomonasaeruginosa. Of the 26 participants with venous ulcers, 22 were included in the cohort and presented a mean age of 57.9 years, ulcers of median duration of 24 months (SD±32.8), covering an area up to 12 cm 2 (63.5%). An 18.2% healing rate was found in the follow-up from 6 to 15 months, with improvement in the condition of the ulcers, as evidenced by decreased total scores in the PUSH (p=0.041). Aggravation in healing conditions was associated with clinical signs of infection in the lesions (p=0.019). Regarding self-care, there was a prevalence of reports of care with feeding and rest, which did not agree with the recommendations in literature, and the use of medications to control systemic diseases. Among the 53 nursing professionals who worked in the units, nursing technicians (56.6%) prevailed. Of the 411 activities referred in the care of people with vascular ulcers, 392 were mapped in theNursing Intervention Classification, with 53.3% corresponding to the “wound/skin control” class, demonstrating that care is focused on the topical treatment of the lesion. In a context of limitations in the care of users, the evolution of the healing of ulcers in follow-up was found favorable, however, the healing rate was significantly low. This context points to the need to reorganize public policies for the care of people with vascular ulcers, as well as the model of management of care to this population.